Upper Bound Limit Stability Analysis for Soil Slope with Nonuniform Multiparameter Distribution Based on Discrete Algorithm - Zhen Wang; Xumeng Yang; Ang Li (Advances in Civil Engineering)
Slope stability analysis is a core issue in geotechnical engineering. This paper proposes a method of upper bound limit stability analysis for a slope with multiparameter coordinated variation based on the comprehensive consideration of the nonuniform distribution of slope soil parameters. This method starts from the perspective of energy balance, establishes a slope failure mechanism which meets velocity separation requirements, deduces its calculation formula for external force power and internal energy dissipation power, develops a cycle program for the most dangerous slip surface searching and stability coefficient calculation through computer programming technology, and finally forms a calculation method of upper bound limit stability analysis for the soil slope with nonuniform multiparameter distribution. At the same time, this method takes a dump slope in an open-pit mine as the engineering background, considers the nonuniformity of density, cohesion, and internal friction angle of the slope soil under subsidence, applies upper bound limit analysis to analyze the slope stability, and evaluates the accuracy of analysis results by using the residual thrust method. The results show that upper bound limit analysis has highly accuracy in stability coefficient calculation; compared with the residual thrust method, the stability coefficient calculation result by upper bound limit analysis is a strict upper bound solution, and the calculation error is easy to be estimated and eliminated. Simultaneously, the most dangerous slip surface obtained by upper bound limit analysis can fully satisfy the velocity separation requirement and has a greater engineering reference value.